Navigating Adolescence: Effectiveness of the YRBSS Tool in Addressing High-Risk Behaviours in India - Dr. Merlyn Grace Ankala, Dr Gurmeet Kaur, Dr Atul Goel (Late), (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Adolescence is a critical developmental stage characterized by rapidtransitions and vulnerability to health-risk behaviors that may persist into adulthood.Monitoring these behaviors is essential for timely interventions. This study assessed theprevalence of high-risk behaviors amongadolescents in Ludhiana, India, and evaluated theeffectiveness of the Youth Risk Behavior Surveillance System (YRBSS) tool in the Indiancontext.